2016
DOI: 10.1177/1756283x16648869
|View full text |Cite
|
Sign up to set email alerts
|

The role of naloxegol in the management of opioid-induced bowel dysfunction

Abstract: Opioid-induced constipation (OIC) and other gastrointestinal (GI) symptoms of opioid-induced bowel dysfunction (OIBD) significantly deteriorate patients’ quality of life and may lead to noncompliance with opioid schedule and undertreatment of pain. Although traditional oral laxatives are the first-line treatment of OIC, they do not address OIBD pathophysiology, and display numerous adverse effects. OIC treatment includes prokinetics (lubiprostone), opioid switch, and changing route of opioid administration. Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Naloxegol is a pegylated modification of naloxone. Naloxegol is a substrate for the blood brain barrier P-glycoprotein transporter and together with its large molecular weight (652 g/mol) limits naloxegol penetration across the blood brain barrier (Bui et al , 2016; Leppert & Woron, 2016). Naloxegol is approved for treatment of opioid-induced constipation especially in non-cancer pain patients (Chey et al , 2014; Leppert & Woron, 2016).…”
Section: Drugs Acting At Opioid Receptors In the Gastrointestinal Tractmentioning
confidence: 99%
“…Naloxegol is a pegylated modification of naloxone. Naloxegol is a substrate for the blood brain barrier P-glycoprotein transporter and together with its large molecular weight (652 g/mol) limits naloxegol penetration across the blood brain barrier (Bui et al , 2016; Leppert & Woron, 2016). Naloxegol is approved for treatment of opioid-induced constipation especially in non-cancer pain patients (Chey et al , 2014; Leppert & Woron, 2016).…”
Section: Drugs Acting At Opioid Receptors In the Gastrointestinal Tractmentioning
confidence: 99%
“…29 Naloxegol, the newest PAM-OR antagonist in the group, has demonstrated positive results in both studies in this review and agrees with the findings of other reviews. 19 Leppert and Woron 19 reported that naloxegol was effective in up to 49% of patients not responsive to standard laxatives and that naloxegol has been shown to be more effective than placebo in patients with OIC and noncancer pain. No studies have been performed in cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…No studies have been performed in cancer patients. 19 The approved dose is 25 mg. 16 Comparison of naloxegol to oral methylnaltrexone is difficult because the primary end points are not the same from the published studies. However, the available data suggest that although both agents are effective, adverse effects occurred at a greater frequency with naloxegol compared with placebo, 36,37 whereas patients who received oral methylnaltrexone had a similar rate of adverse effects as the placebo group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical efficacy of naloxegol for the treatment of OIC has been demonstrated in several clinical studies. 26,31,79,80 Following oral administration, the C max of Movantik ® is achieved in less than two hours, with a secondary peak 0.4-3 hours later. Of note, clinical efficacy in patients not responsive to laxatives has been demonstrated in patients with OIC and non-malignant pain.…”
Section: Naloxegol (Movantik® Previously Nktr-118)mentioning
confidence: 99%